2017
DOI: 10.14687/jhs.v14i1.4314
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cooperative learning on academic achievement: A meta-analysis on the relationship between the study group size and effect size<p> İşbirlikli öğrenmenin başarıya etkisi: Çalışma grubu ile etki büyüklüğü arasındaki ilişkiye dair bir meta analiz çalışması

Abstract: The purpose of this study was to determine the effect of cooperative learning on achievement and the relationship between the study group and effect size by means of meta-analysis. Metaanalysis is the method employed in order to statistically analyze the quantitative data collected in independent and multiple studies carried out on similar topics, and to reach a general judgment regarding the results of these studies. Certain criteria were used in order to decide which researches would be included in the meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…It is seen that other results supporting the results of the research are gathered from the meta-analysis studies conducted on individual effects of student-centered strategies, methods, and techniques. In these researches, cooperative learning (Biçer, 2017;Capar & Tarım, 2015;Hattie, 2009;Jonhnson, Johnson & Stanne, 2000; Öğrenci Merkezli Strateji, Yöntem ve Tekniklerin Akademik Başarıya Etkisi: Bir Meta-Analiz Çalışması 209 Kyndt et al, 2013;Savelsbergh et al, 2016;Schroeder et al, 2007;Springer et al, 1999;Şen & Yılmaz, 2013;Tarım, 2003;Tuncer & Dikmen, 2017), problem-based learning (Ayaz, 2015;Vernon & Blake 1993;Zhou et al, 2016) and project-based learning (Ayaz & Söylemez, 2015) were found to be more efficient in increasing academic achievement when compared to the teacher-centered approaches. In addition to this, studies conducted at secondary and tertiary level were commonly found to have a higher level of effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is seen that other results supporting the results of the research are gathered from the meta-analysis studies conducted on individual effects of student-centered strategies, methods, and techniques. In these researches, cooperative learning (Biçer, 2017;Capar & Tarım, 2015;Hattie, 2009;Jonhnson, Johnson & Stanne, 2000; Öğrenci Merkezli Strateji, Yöntem ve Tekniklerin Akademik Başarıya Etkisi: Bir Meta-Analiz Çalışması 209 Kyndt et al, 2013;Savelsbergh et al, 2016;Schroeder et al, 2007;Springer et al, 1999;Şen & Yılmaz, 2013;Tarım, 2003;Tuncer & Dikmen, 2017), problem-based learning (Ayaz, 2015;Vernon & Blake 1993;Zhou et al, 2016) and project-based learning (Ayaz & Söylemez, 2015) were found to be more efficient in increasing academic achievement when compared to the teacher-centered approaches. In addition to this, studies conducted at secondary and tertiary level were commonly found to have a higher level of effect.…”
Section: Resultsmentioning
confidence: 99%
“…Araştırma bulgularını destekleyen diğer sonuçların öğrenci merkezli strateji, yöntem ve tekniklerin bireysel etkisine yönelik gerçekleştirilen meta-analiz çalışmalarından elde edildiği görülmektedir. Bu araştırmalarda; işbirliğine dayalı öğrenme (Biçer, 2017;Capar ve Tarım, 2015;Hattie, 2009;Jonhnson, Johnson ve Stanne, 2000;Kyndt ve diğerleri, 2013;Savelsbergh ve diğerleri, 2016;Schroeder ve diğerleri, 2007;Springer ve diğerleri, 1999;Şen ve Yılmaz, 2013;Tarım, 2003;Tuncer ve Dikmen, 2017), probleme dayalı öğrenme (Ayaz, 2015;Vernon ve Blake 1993;Zhou ve diğerleri, 2016) ve proje tabanlı öğrenme (Ayaz ve Söylemez, 2015) gibi yöntemlerin, öğretmen merkezli yaklaşımlara göre akademik başarıyı artırmada daha etkili olduğu belirlenmiştir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
See 1 more Smart Citation
“…Gerçekleştirilen analizler sonucunda iş birlikli öğrenme yaklaşımının Matematik dersi akademik başarısı üzerinde orta düzeyde bir etkiye sahip olduğu sonucuna ulaşılmıştır (d=0.59). Tuncer ve Dikmen (2017) iş birlikli öğrenmenin başarı üzerindeki etkisini incelediği araştırmasında 2003-2011 yılları arasında gerçekleştirilen 6 farklı araştırmayı meta-analize dahil etmiş ve iş birlikli öğrenmenin başarı üzerinde orta düzeyde bir etki sahip olduğu sonucuna ulaşmıştır (d=0,518) . Aynı şekilde Karakuş ve Öztürk (2016) de işbirliğine dayalı öğrenme yaklaşımının Fen dersi akademik başarısı üzerindeki etkisini inceleyen 30 araştırmayı meta analiz yöntemiyle incelemiş ve bu inceleme sonucunda işbirliğine dayalı öğrenme yaklaşımının öğrencilerin Fen dersi akademik başarısı üzerinde olumlu yönde orta düzeyde bir etkiye (d=0.694) sahip olduğunu ifade etmişlerdir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…When the literature is examined, it is seen that different methods and approaches in field education research are tried by making various research designs and the benefits and limitations of using these different methods are discussed. Computer-assisted education (Dinçer, 2015), creative drama (Ulubey and Toraman, 2015), brain-based learning (Gözüyeşil and Dikici, 2014), project based learning (Ayaz and Söylemez, 2015), cooperative learning (Tuncer and Dikmen, 2017) applications are tested by meta-analysis method in many fields such as mathematics (Kaplan, Duran and Baş, 2015;Sad, Kis, Demir and Özer, 2016), geometry (Günhan and Açan, 2016), social studies (Yaşar, Köse, Göz and Bayır, 2015), science education (Öztürk and Karakuş , 2016;Ural and Bümen, 2016), geography (İnel and Sezer, 2017). In this way, meta-analysis studies increase the generalizability thanks to the unification of the results of the studies conducted in the field and increase the sample size, and thus contribute to reaching more valid and reliable results (Borenstein et al, 2009).…”
Section: Introductionmentioning
confidence: 99%